Multiphysics Analysis of Thermal Deformation Effects on a Waveguide Bandpass Filter - Davide Guarnera; Giorgio S. Mauro; Santi Concetto Pavone; Tommaso Isernia; Gino Sorbello (IEEE Access)
In this paper, we propose a multiphysics analysis of thermal deformation effects on the frequency response of a Chebyshev bandpass filter designed for C-band satellite communications (SATCOM). Indeed, the design of microwave devices for SATCOM must account for the effects of thermal gradients on frequency response and incorporate suitable compensation techniques. The proposed analysis consists of appropriate sequence of electromagnetic, thermal, and mechanical simulations to evaluate the filter thermal profile as a function of input power, the resulting mechanical deformations, and the consequent effect on the filter frequency response. The results obtained are related to the filter equivalent circuit model to obtain deeper insight of the involved physical phenomena and useful information for the design of the most suitable compensation strategy. Finally, to demonstrate the effectiveness of multiphysics analysis in the optimal design of devices robust to thermal gradients, a thermally compensated bandpass filter using passive heat sinks is designed and validated.